AGRONOMIC TRAITS OF LOCAL WETLAND RICE VARIETIES IN JAMBI PROVINCE - Julistia Bobihoe (SEAMEO BIOTROP, 2021)
Indonesia’s swamplands are among the areas earmarked for future agricultural development. As a type of wetland, swamplands are periodically inundated and have soil properties that are uniquely different from other agroecosystems. In Indonesia, some of these areas are currently used for rice cultivation, representing the country’s very diverse genetic resources of local rice varieties. Most farmers continue to plant and cultivate local swampland rice varieties because of their ability to adapt to extreme environments. This study on the agronomic traits of local swampland rice varieties was conducted to evaluate their agronomic characteristics and to identify varieties with superior quality traits. The research was carried out from April to October 2016 using a single-plot method at Rantau Kapas Mudo Village, Batanghari Regency, Jambi Province. Eleven rice varieties were planted in 10 × 5 m single plots, with a spacing of 25 × 25 cm and a distance of 1 m between plots. The eleven genetic resources of local swampland rice varieties included Serendah Halus, Rimbun Daun, Karya, Serendah Bawang, Sereh Aek, Botol, Pontianak, Semut, Dawi, Ketan Itam, and DI. The observed characters consisted of plant height at harvest, number of productive tillers, age at harvest, number of grains per panicle, number of filled grains per panicle, number of empty grains per panicle, weight of 1,000 grains, seed shape, and production volume. Differences were observed among the local swampland rice varieties. The highest production volume (3.32 tonnes ha⁻¹) was obtained from the Rimbun Daun variety, followed by 2.86 tonnes ha⁻¹ from the Dawi variety. These two varieties showed strong potential to become leading regional swampland rice varieties.